Evaluating the Effectiveness of Personalized Learning Approaches in TVET Colleges - Chika Oliver Ujah (International Journal of Home Economics, Hospitality and Allied Research)
This review examines how personalized learning strategies affect Technical and Vocational Education and Training (TVET) colleges. Personalized learning is an adaptive instructional model that tailors educational experiences to meet the unique needs of each student. It has garnered significant attention for its potential to address the varied learning profiles of TVET learners. The review carefully evaluates existing literature to pinpoint key strategies, challenges, and outcomes related to personalized learning within the TVET context. A thorough methodology is employed to analyze peer-reviewed articles, conference proceedings, and pertinent grey literature from the past decade. Key areas of focus include the impact of personalized learning on student engagement, skill development, academic success, and job readiness. Furthermore, the review investigates the technological tools and teaching frameworks that facilitate personalized learning in TVET settings, while also considering obstacles such as limited resources, teacher preparedness, and policy issues. Initial findings indicate that personalized learning methods can boost student motivation, enhance learning results, and promote career readiness among a diverse group of TVET students. Nonetheless, the evidence is still scattered, highlighting the urgent need for more research on effective and sustainable implementation strategies. The primary goal of this review is to lay the groundwork for future studies.